AERODYNAMICS OF INDUSTRIAL BUILDINGS - Petrov, V.; Gоncharenko, D.; Zhdanov, O. (Zernovì produkti ta kombìkorma, 2024)
The design of metal silos and other structures (towers, silo galleries) of the grain receiving point under the influence of wind load is considered in the work. The positive and negative aspects of the structures of the silos under consideration have been identified. The method of researching wind load on silos in the ANSYS CFX package was applied. A three-dimensional model of industrial buildings was made and, taking into account the recommendations, the estimated volume around the research object was adopted. The volume for air movement around industrial buildings is also defined. Taking into account the method of finite elements, a grid was built on the layout of the research object. Assigned initial data and boundary conditions. The structure of six metal silos with a diameter of 15.2 m and a height of a cylindrical wall of 12 m of the Drokiivskyi HPP (Republic of Moldova) was taken as the object of the study. Wind pressure on cylindrical walls and conical roofs is estimated by the finite element method using the ANSYS CFX package for wind direction perpendicular to the line of silos at maximum speed. Pressure isobars are found in various auxiliary vertical and horizontal planes. Lines of equal air flow velocities and their vector analogues are constructed. Zones of maximum and minimum pressure on industrial facilities have been established. The correspondence of the general picture of the pressure distribution along the wall in the circumferential direction when the aerodynamic coefficient changes is established. Determined wind loads on structural elements of industrial buildings. Calculations were performed using the functional calculator built into this ANSYS CFX package. To verify the numerical consistency of the obtained results, additional research is required. Due to the movement (animation) of auxiliary vertical planes, it is possible to consider the dynamics of changes in pressure and velocity of the incoming air flow in the calculated volume.